Effects of Sociographic and Personal Factors on Food Purchasing in Traditional Markets - Nurliza, Nurliza (ETIKONOMI, 2025)
Research Originality: The current literature lacks a structured analysis of how interactions between lifestyle factors and sociodemographic changes impact food purchasing behavior in traditional markets. By analyzing these factors, businesses can optimize product selections, refine marketing strategies, and enhance customer engagement to align with the diverse preferences and requirements of their target market, adapting to both current trends and future changes.Research Objectives: This study employs a psychodynamic approach, the theory of personality traits, two-way physical and perceptual interactions, and household assumptions to examine how sociographic lifestyle, household characteristics, and personality traits influence food purchasing behavior. Research Methods: The mixed methods, which included in-depth interviews with 183 household customers, utilized non-probability sampling and partial least squares structural equation modeling.Empirical Results: Increased food purchasing behavior is caused by changing sociographic lifestyles rather than personality traits and household characteristics. A greater sociodemographic lifestyle, personality traits, and household characteristics correspond to increased friendship, values, responsible spending, and household size.Implications: Food safety regulations must be implemented effectively, which includes appointing market management authorities, as agencies in the informal food sector are often underfunded and unregulated.JEL Classification: D1, E21, L66, R2How to Cite:Nurliza. (2025). Consumers in Traditional Markets: Sociographic Lifestyle, Household Features, and Personality Traits. Etikonomi, 24(1), 205 – 220. https://doi.org/10.15408/etk.v24i1.38288.